2009
DOI: 10.1002/cncr.24173
|View full text |Cite
|
Sign up to set email alerts
|

Prognostic significance of occult axillary lymph node metastases after chemotherapy‐induced pathologic complete response of cytologically proven axillary lymph node metastases from breast cancer

Abstract: Persistent occult axillary lymph node metastases were not uncommon in patients with axillary lymph node-positive LABC who experienced a pCR in involved lymph nodes after preoperative chemotherapy. However, such occult metastases did not adversely affect the good prognosis associated with axillary lymph node pCR. Therefore, routine lymph node CK evaluation was not recommended after primary chemotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 22 publications
1
23
0
Order By: Relevance
“…Some studies have reported some factors as predictors for non sentinel lymph node involvement such as metastasis size in SN tumor size and number of involved SNs (Van Zee et al, 2003;Ryden et al, 2007). Presence of at least one tumor positive non sentinel node in patients with negative SN is also reported in previous studies but no negative prognostic effect has been declared in such situations (Weaver et al, 2000;Loya et al, 2009;Krag et al, 2010).…”
Section: Discussionsupporting
confidence: 56%
See 1 more Smart Citation
“…Some studies have reported some factors as predictors for non sentinel lymph node involvement such as metastasis size in SN tumor size and number of involved SNs (Van Zee et al, 2003;Ryden et al, 2007). Presence of at least one tumor positive non sentinel node in patients with negative SN is also reported in previous studies but no negative prognostic effect has been declared in such situations (Weaver et al, 2000;Loya et al, 2009;Krag et al, 2010).…”
Section: Discussionsupporting
confidence: 56%
“…Our data also revealed that IHC staining just detected more isolated tumor cells than multilayer sectioning. The need for ALND in breast cancer patients with micrometastasis and /or ITCs in the absence of macrometastasis remains controvertial .While some authors believe micrometastasis /ITCs is associated with poorer disease free and overall survival (Van Zee et al, 2003;Lyman et al, 2005;Loya et al, 2009;Krag et al, 2010) other studies support the theory that ALND might be avoided in these patients (26,27,28,29). Relying upon the latter's opinion, ITC do not worsen patients' prognosis (Ryden et al, 2007).…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, pCR without any residual tumor in both breast and axillary lymph nodes after neoadjuvant chemotherapy is strong independent predictor of improved survival [24][25][26]. The studies in the literature showed that the rates of pCR have been much lower and have generally been less than 20% [27][28][29].…”
Section: Discussionmentioning
confidence: 97%
“…In our study also, there was a significant difference in the outcome between complete and partial pathological responders. On the other hand, some studies demonstrated that patients who had pCR in axillary lymph nodes but not in primary tumor of breast was an independent factor for outcome rather than pCR in breast only [21,24,28,31]. A study stated that pCR in axilla was associated with an excellent prognosis, even with a residual primary tumor, pointing to biologic differences between primary and metastatic cells [32].…”
Section: Journal Of Surgical Oncologymentioning
confidence: 94%
“…Photographic documentation of sampling is extremely helpful in this respect and for accurate evaluation of the status of resection margins (Figure 1). The examination of sentinel lymph node after NAT should be as accurate as possible, but molecular test (such as One Step Nucleic Acid Amplification assay, ie, OSNA (19)) and immunocytochemistry for cytokeratins are not recommended (20).…”
Section: Gross Handling and Reporting Of Surgical Specimens After Natmentioning
confidence: 99%